Differences between 201T1 and 43K Tissue Distribution in Rested and Exercised Rats - Llaurado, J. G.; A. Madden, Jane; Smith, G.A. (Nuklearmedizin - NuclearMedicine, 1981)
A comparison is made of relative organ-to-plasma uptake of 43K and 201T1 in rats at rest and after exercise (two hour swimming). Organs were obtained 0.5 or 3 hrs after radionuclide injection. Thus, there were four groups each for 43K and 201T1. For 201Tl the triad kidneys-heart-adrenals was very consistent throughout the four experimental situations in showing the highest uptake, whereas for 43K adrenals-heart-liver predominated at 0.5 hrs and thymus-liver at 3 hrs. The ratio 201Tl/43K in myocardium was always greater than unity in all four experimental situations. The heart-to-lung and heart-to-liver uptake ratios were lower in all cases for 43K vs. 201T1. One of the most important findings was that exercise always determined an increase of these ratios for 201T1, but it had an unfavorable effect on the 43K heart/lung ratio and no definite effect on the 43K heart/liver ratio. Our findings are analyzed in the light of previous publications. It is concluded that these two ions have biologically important different characteristics and that excessive and seemingly unjustified emphasis has been made on their physiological similarity.